Analysis of the therapeutic effect of Midrimax® on accommodation overstrain in patients with orthokeratological correction - M. V. Makhova (Российский офтальмологический журнал)
Purpose: a year-long study of the accommodative function of the eye in patients with orthokeratologic (OK) correction, and the analysis of the therapeutic effect of the drug Midrimax® on accommodation overstrain in patients with OK lenses.Material and methods. The study group included 88 patients (176 eyes) with progressive myopia and OK lenses. The control group included 108 patients (216 eyes) who had optical correction with monofocal glasses and soft contact lenses. During the year, the accommodative function of patients of these two groups was studied using a Speedy-I Accommodograph that involved the calculation of accommodative coefficients: the coefficient of accommodative response and the coefficient of accommodative microfluctuations (CMF). The accommodographic examination in the study group was conducted before wearing OK lenses, after 1 month, 6 months and a year of wearing OK lenses. In the control group, the study of accommodation was carried out after 6 and 12 months. To assess the nature of the effect of Mydrimax® on accommodation overstrain, 70 children (140 eyes) with OK correction and varying degrees of accommodation overstrain were examined. A control group and a study group of 35 people (70 eyes) each were formed. In the study group, Mydrimax® was instilled daily before going to bed, 2 drops in each eye for 30 days. The study of accommodation on the Speedy-i accommodograph was conducted before treatment and after 30 days of treatment.Results. Before wearing OK lenses, 50.5 % had normal accommodative function, 33 % revealed lack of accommodation and only 16.5 % had various degrees of accommodation overstrain. After 6 months of using OK lenses, the accommodation pattern changed: 33.5 % of patients retained normal accommodation function, in 15.5 % of cases accommodation insufficiency decreased, but the number of patients (51.0 %) with accommodation overstrain of varying degrees increased. During the next 6 months of wearing OK lenses, the state of accommodation practically did not change: 39.5 % retained normal accommodative function, 10.5 % had insufficient accommodation and 49.5 % accommodation overstrain. The course of treatment with Mydrimax® for 30 days in patients with OK correction was effective at any degree of accommodation overstrain.Conclusion. The use of OK lenses stimulates accommodation by reducing the number of patients with accommodation insufficiency and increasing the number of patients with accommodation overstrain. The use of Mydrimax® for a course of 30 days is effective in patients with OK correction at any degree of accommodation overstrain.